2020
DOI: 10.14198/jhse.2021.161.10
|View full text |Cite
|
Sign up to set email alerts
|

The effects of betalain-rich concentrate supplementation in attenuating muscle damage following eccentric exercise

Abstract: Betalains are bioactive pigments that have been shown to reduce muscle damage and enhance recovery from exercise. However, to date, studies have examined the effects of betalains on aerobic exercise alone, and thus, their possible benefits for muscle damage recovery following eccentric exercise is unknown. We, therefore, aimed to examine the effects of a betalain-rich concentrate (BRC) on indices of muscle damage following eccentric exercise. Eleven healthy, recreationally active males were randomly assigned i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…The present study found that Sw-T and muscle soreness decreased significantly after BRJ supplementation. One possible explanation for the significant improvement in wall-sit performance and non-significant VSFT is the reduction in muscle soreness and related mechanisms, such as the reduction in tissue swelling [38,46]. In fact, muscle soreness is associated with symptoms such as reduced muscle force production, pain, mechanical damage to skeletal muscles, and tissue edema [38,46,47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study found that Sw-T and muscle soreness decreased significantly after BRJ supplementation. One possible explanation for the significant improvement in wall-sit performance and non-significant VSFT is the reduction in muscle soreness and related mechanisms, such as the reduction in tissue swelling [38,46]. In fact, muscle soreness is associated with symptoms such as reduced muscle force production, pain, mechanical damage to skeletal muscles, and tissue edema [38,46,47].…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for the significant improvement in wall-sit performance and non-significant VSFT is the reduction in muscle soreness and related mechanisms, such as the reduction in tissue swelling [38,46]. In fact, muscle soreness is associated with symptoms such as reduced muscle force production, pain, mechanical damage to skeletal muscles, and tissue edema [38,46,47]. Furthermore, nitrate-rich dietary supplements, such as BRJ, have been reported to play a vital role in improving neuromuscular efficiency, especially during fatigue [48].…”
Section: Discussionmentioning
confidence: 99%
“…An a priori power analysis was conducted using statistical software (G*Power 3.1.9.2, Dusseldorf, Germany) to determine the minimum sample size required to find statistical significance. With a desired power of 0.80, an alpha of level of 0.05, and a moderate effect size of 0.25 [ 39 , 40 ], it was determined that 24 participants would be required. Using word-of-mouth and email, participants were recruited from Texas Woman’s University and the University of North Texas.…”
Section: Methodsmentioning
confidence: 99%